2010
DOI: 10.1016/j.jedc.2010.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Technological leadership and persistence of monopoly under endogenous entry: Static versus dynamic analysis

Abstract: a b s t r a c tWe build a dynamic oligopoly model with endogenous entry in which a particular firm (leader) invests in an innovation process, facing the subsequent entry of other firms (followers). We identify conditions that make it optimal for the leader in the initial oligopoly situation to undertake pre-emptive R&D investment (strategic predation) eventually resulting in the elimination of all followers. Compared to a static model, the dynamic one provides new insights into the leader's intertemporal inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Etro () has analyzed optimal unilateral screening contracts in markets with endogenous entry, showing that a firm would always gain from committing to aggressive incentive contracts (with extra effort required from all types) to limit entry and gain market shares over the competitors. Although that model, following the analysis of leadership with endogenous market structures (as in Etro, or Kováč et al., ), neglected contract competition, a similar outcome is likely to emerge also in the present context. Finally, one could investigate welfare analysis in our more complex environment…”
Section: The Modelmentioning
confidence: 90%
“…Etro () has analyzed optimal unilateral screening contracts in markets with endogenous entry, showing that a firm would always gain from committing to aggressive incentive contracts (with extra effort required from all types) to limit entry and gain market shares over the competitors. Although that model, following the analysis of leadership with endogenous market structures (as in Etro, or Kováč et al., ), neglected contract competition, a similar outcome is likely to emerge also in the present context. Finally, one could investigate welfare analysis in our more complex environment…”
Section: The Modelmentioning
confidence: 90%
“…The related literature [24,[27][28][29][30] has not considered initial marginal cost levels that exceed the choke price nor has it carried out a global analysis. In all these papers, any of the initial (permissible) technologies will be developed to full materialization; technologies that are only developed under specific regimes (i.e., product market collusion) remain hidden.…”
Section: ]mentioning
confidence: 99%
“…What appear to be predatory strategies by market leaders can actually be welfare improving as long as the entry of followers is endogenous: for instance, these are the cases analyzed by Creane and Konishi () on unilateral technology transfers, by Kováč et al . () on cost reducing investments that limit entry and Etro () on bundling of a primary good sold in monopoly with a secondary one sold in competition. Ino and Matsumura () have shown that, contrary to common wisdom, leadership by one firm induces always beneficial concentration in markets with homogenous goods and endogenous entry, in the sense that it increases both the Herfindahl‐Hirschman Index of concentration and welfare.…”
Section: Inside the Black Box Of The Market Structurementioning
confidence: 99%